Relationship between body mass index and perceived insufficient sleep among U.S. adults: an analysis of 2008 BRFSS data - Croft Janet B; Presley-Cantrell Letitia R; McKnight-Eily Lela R; Chapman Daniel P; Perry Geraldine S; Wheaton Anne G (BMC, 2011)
Abstract Background Over the past 50 years, the average sleep duration for adults in the United States has decreased while the prevalence of obesity and associated outcomes has increased. The objective of this study was to determine whether perceived insufficient sleep was associated with body mass index (BMI) in a national sample. Methods We analyzed data from the 2008 Behavioral Risk Factor Surveillance System (BRFSS) survey (N = 384,541) in which respondents were asked, "During the past 30 days, for about how many days have you felt you did not get enough rest or sleep?" We divided respondents into six BMI categories and used multivariable linear regression and logistic regression analyses to assess the association between BMI categories and days of insufficient sleep after adjusting for sociodemographic variables, smoking, physical activity, and frequent mental distress. Results Adjusted mean days of insufficient sleep ranged from 7.9 (95% confidence interval [CI]: 7.8, 8.0) days for people of normal weight to 10.5 (95% CI: 10.2, 10.9) days for those in the highest weight category (BMI ≥ 40). Days of perceived insufficient sleep followed a linear trend across BMI categories. The likelihood of reporting ≥14 days of insufficient sleep in the previous 30 days was higher for respondents in the highest weight category than for those who were normal weight (34.9% vs. 25.2%; adjusted odds ratio = 1.7 (95% CI: 1.5, 1.8]). Conclusion Among U.S. adults, days of insufficient rest or sleep strongly correlated with BMI. Sleep sufficiency should be an important consideration in the assessment of the health of overweight and obese people and should be considered by developers of weight-reduction programs.